A highly sensitive and selective fluorescent chemosensor for the sequential recognition of Zn2+ and S2− in living cells and aqueous media - Yun, Jin Yeong; Jo, Tae Geun; Han, Jiyeon; Jang, Hyo Jung; Lim, Mi Hee; Kim, Cheal (Sensors and actuators. B, Chemical, 2018)
A new highly selective chemosensor 1 (E)-5-((2-hydroxybenzylidene)amino)-1H-imidazole-4-carboxamide was designed and synthesized for the sequential recognition of Zn2+ and S2− in a near-perfect aqueous media. The sensor 1 exhibited a green color fluorescence in the presence of Zn2+. The detection limit (1.18μM) of 1 for Zn2+ is much lower than World Health Organization guideline (76μM) in drinking water. 1 can detect and quantify Zn2+ in real water samples and the sensing mechanism of Zn2+ by 1 was explained by DFT calculations. Moreover, resulting 1-Zn2+ complex can detect hydrogen sulfide through turn-off fluorescent change, without any anion interference. The detection limit (2.60μM) of 1-Zn2+ complex for S2− was much lower than EPA guideline (7.8mM) by odor in drinking water. Furthermore, sensor 1 could detect sequentially Zn2+ and S2− in living cells.